The relationship between multidirectional jumping and performance in change of direction tasks - Bourgeois, F. A.; Gamble, P.; Gill, N. D.; McGuigan, M. R. (The Journal of Strength and Conditioning Research, 2018)
This study investigated the test-retest reliability of 2 change of direction (COD; 180 and 45° COD) sprints and 3 multidirectional jump (MDJ) tests. Variables examined were approach time (sprint before plant-step), exit time (sprint after plant-step), total time (time to completion) and MDJ approach time, and distance, respectively. Second, the ability of MDJ tests to predict performance in COD tests was examined. Twenty men (age: 27.5 ± 5.9 years; height: 1.79 ± 0.1 m; and body mass: 79.1 ± 12.0 kg) performed 5 trials for each assessment, executing left plant-leg (LT) and right plant-leg (RT) steps, on 2 testing occasions separated by 7 days. Between-session and within-session intraclass correlation coefficients (ICCs) and coefficients of variation (CVs) for all measurements were calculated. Usefulness of COD and MDJ tests was assessed using typical error and smallest worthwhile change (SWC) comparison. Results showed only one MDJ measurement generated unstable between-session reliability. Within-session reliability of approach and exit COD times, and MDJ approach times possessed confidence limits (90% CL) that extended below 0.75 ICC. All COD total times and MDJ distances presented high reliability (ICC = 0.87-0.99) with low CV (0.9-4.1%). Right-leg MDJ distances were predictors of RT COD performances (r = 0.50-0.68, p = 0.001-0.024), whereas LT MDJ distances were predictors of LT180 COD performance (r = 0.67-0.71, p = 0.001). All measurements were useful in detecting SWC in performance. These findings suggest the COD tests and MDJ distances are reliable for assessing and monitoring COD performance in similar cohorts.